Delusional Parasitosis : Series Of 25 Cases - Bhatia M S; Shome S; Choudhary Sandeep; Gautam R K (Wolters Kluwer Medknow Publications, 1996)
A series 25 cases of delusional parasitosis is being reported. There were three cases below 45 years, 12 cases between 46-45 years and 11 cases above 55 years of age, 64% cases were females. A majority of cases (92%) had insidious onset. The duration of symptoms in all the cases (except one) was 6 months or more. 13 cases presented with infestation with insects over body and 10 cases with insects crawling over scalp. There were three cases each with diabetes mellitus and leprosy. Three cased had dementia, 2 cases had depression and one case presented with trichotillomania. Pimozide was used in22 cases, amitriptyline in 2 cases and fluoxetine in one. 14 cases (52%) showed complete remission while receiving drug, 8 cases showed partial improvement and 3 cases did not respond.